Analisis Penggunaan Akun Instagram @melekteknologi.id dalam Memenuhi Kebutuhan Informasi Mahasiswa Ilmu Perpustakaan Stambuk 2018 - Ritonga, Sahpriani; Rohani, Laila; Yusniah, Yusniah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to explore the use of Instagram accounts in meeting the information needs of Library Science students and to identify the challenges experienced by Library Science students. The method used in this study is qualitative with a descriptive approach that uses interviews to collect data directly from informants in order to gain a deep understanding of how the Instagram account @melekteknologi.id meets the information needs of Library Science students Stambuk 2018. Data collection techniques include observation, interviews, and documentation. In addition, the researcher also interviewed followers of the Instagram account @melekteknologi.id. The results of the study show that all the informants interviewed follow the Instagram account @melekteknologi.id and use the information available according to their needs. Challenges faced by the informants include unstable networks, limited mobile data, and information on the account getting buried.